Screening of a ScFv Antibody With High Affinity for Application in Human IFN-γ Immunoassay - Yang, Hang; Zhong, Yanfang; Wang, Juncheng; Zhang, Qinghong; Li, Xiulan; Ling, Sumei; Wang, Shihua; Wang, Rongzhi (Frontiers in Microbiology, 2018)
Interferon gama (IFN-γ), a signal proinflammatory cytokine secreted by immune cell, and plays a critical role in the pathogenesis and progression of many diseases. It has been regarded as an important marker for determination of disease-specific immune responses. Therefore, it is urgent to develop a feasible and accurate method to detect IFN-γ in clinic real blood samples. Until now, the immunoassay based on scFv antibody for human IFN-γ is still not reported. In the present study, an scFv antibody named scFv-A8 with high specificity was obtained by phage display and biopanning, with the affinity 2.6×109 L/mol. Maltose binding protein(MBP) was used to improve the solubility of scFv by inserting an linker DNA between scFv and MBP tag, and the resulted fusion protein (MBP-LK-scFv) has high solubility and antigen biding activity. The expressed and purified MBP-LK-scFv antibody was used to develop the indirect competitive ELISA (ic-ELISA) for detection of human IFN-γ, and the result indicated that the linear range to detect IFN-γ was 6-60 pg/mL with IC50 of 25 pg/mL. The limit of detection was 2 pg/mL (1.3 fm), and the average recovery was 85.05%, further demonstrating that the detection method based on scFv has higher recovery and accuracy. Hence, the developed ic-ELISA can be used to detect IFN-γ in real samples, and it may be further provided a scientific basis for disease diagnosis.